Epidemiologic aspects and risk factors associated with infertility in women undergoing assisted reproductive technology (ART) in north of Iran - Zamaniyan, Marzieh; Gordani, Noushin; Bagheri, Paniz; Jafari, Kaveh; Peyvandi, Sepideh; Hajihoseini, Mojtaba; Taheripanah, Robabeh; Moradi, Siavash; Peyvandi, Salomeh; Alborzi, Arman (Clinical Journal of Obstetrics and Gynecology, 2021)
Objective: This study aimed to investigating of the epidemiological aspects of infertility and related risk factors in infertile women. Materials and methods: This cross-sectional study, carried out on 330 infertile women referred to two infertility treatment center of Imam Khomeini Hospital and Mother center in Sari, Iran, from April 2015 to March 2017. Results: 54.5% of these women were in the age of 30-39 years, infertility duration in 55.2% was 1-5 years, Body mass index (BMI) in 44.5% of samples was 26-30 kg/m2, 54.5% had diploma and associate degree. 63.6% lived in urban areas. 74.5 % of patients reported primary infertility. History of polycystic ovarian syndrome (PCOs) and pelvic inflammatory disease (PID) and poor ovarian reserve were the most common causes and risk factors for the infertility with prevalence 19.42%, 16.81% and 13.91%, respectively. Most underlying disease was thyroid disorders (54.5%). There was found statistically significant relationship between residents of urban areas and infertility duration, endometriosis and educational levels, miscarriage with thyroid. Data analysis performed using IBM SPSS 21 software and Chi-Square test (p < 0.05). Conclusion: The results showed that women with infertility in north of Iran were more likely to be older, less educated, and also had overweight. They are more possible to have ovarian disorders. In these area, thyroid disease more common like Iodine deficient regions. Future research should be focused on the reasons why majority of women don’t seek treatment for the underline significant diseases that may be effects on ovarian function and fertility.